THE STUDY ON PHYSICAL AND NON-PHYSICAL IMPACT OF DANA DESA IN OEMASI VILLAGE NEKAMESE KUPANG-NTT - M.E. Perseveranda; Emiliana Martuti Lawalu (Jurnal REP (Riset Ekonomi Pembangunan), 2022)
All villages in Indonesia received what so-called Dana Desa, and Oemasi village is no exception. In spite of any obstacles, several evidences have showed that the Dana is impactful. The impactful objects want to point is all pertinent to physical developments and that of non-physical one. In addition, various outputs of public facilities in the village have set forth easiness for village community or at least improving their quality of life. Judging the impactful objects will be the extent of this research. In these regard, such impacts would be measured by reading documents related and making interviews directly to the key informants. In addition, for making sense the data then the qualitative analysis is helpful for the reason, it can also find other aspects related with all village affairs.